Uncertainty of stress path in fault stability assessment during CO2 injection: Comparing smeaheia 3D geomechanics model with analytical approaches. (May 2023) - Choi, Jung Chan; Skurtveit, Elin; Huynh, Khoa D.V.; Grande, Lars
Highlights: This study highlights the limitation of uniaxial strain assumptions in fault stability assessments for CO2 injection sites, revealing that this simplified approach underestimates the change in effective horizontal stress. Discrepancies between 3D geomechanics simulations and uniaxial strain assumptions are largest when bounding faults are juxtaposed with softer materials, emphasizing stiffness contrast importance. The uniaxial strain assumption overlooks critical scenarios for fault stability assessments due to its inability to account for lateral deformation on the fault/reservoir boundary. To correct uncertainties caused by the uniaxial strain assumption, the study suggests calibrating the fault stability assessment by 30% for a base case and 60% for a conservative assessment when bounding faults are juxtaposed with low-stiffness shale formation under a normal stress regime. Abstract: This study investigates the limitation of simplified stress path assumptions, particularly uniaxial strain conditions, in fault stability assessments for CO2 injection sites. We conducted a 3D geomechanics simulation for the Smeaheia fault block in the Norwegian North Sea and compared the results with simplified stress path assumptions. Our results indicate that the uniaxial strain assumption underestimates the change in effective horizontal stress, particularly for bounding faults subjected to a significant change in pore pressure gradient with soft surroundings. Rotations of maximum horizontal stresses parallel to soft surroundings are also observed along the bounding faults due to the directional difference in stiffness contrast along faults. This underestimation results in overestimation of fault stability by up to 60% for an extreme case. Our study thus highlights that the uniaxial strain assumption, which limits to account for lateral deformation on the fault/reservoir boundary, overlooks critical changes in the effective horizontal stress and associated critical scenarios for fault stability assessments. When bounding faults are juxtaposed with low-stiffness shale formation under a normal stress regime, calibrating the fault stability assessment by 30% for a base case and 60% for a conservative assessment can provide a practical way to correct the uncertainties caused by using uniaxial strain assumption.